Application of Designing Economic Mechanisms to Power Market - Part 1 Generation Side Power Market Design - XIE Qingyang; ZHU Yonggang; YING Liming (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The paper studies on the core philosophy and algorithm of the designing economic mechanisms theory, a new algorithm of designing incentive compatible power market mechanisms is proposed, a generation side power market mechanism model which has features of inventive compatibility, informationally efficient and decentralized decision is constructed. The power market based on the designing economic mechanisms theory can lead to the Pareto Optimality of the resource allocation; meanwhile GENCOs are permitted to pursue profits maximization. The paper is in two parts. Part 1 focuses on the process of constructing a generation side power market competitive mechanism model based on the designing economic mechanisms theory. Part 2 presents the characteristic analysis of the generation side power market competitive mechanism. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2369